UV fixing glue for fixing photovoltaic module, preparation method and application
By adjusting the ratio of reaction diluent and photoinitiator, adding vapor phase silica, and using highly reactive resins and monomers, the oxygen resistance and bright lines and yellowing problems of UV fixing glue are solved, and the rapidity of UV fixing glue is achieved. Photocuring and high stability extend the service life of photovoltaic modules.
Patent Information
- Application Number
- CN202411422600.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
The existing UV fixing glue has oxygen resistance to polymerization during photocuring, which leads to poor curing, affecting the contact quality of the welding tape and the battery cell, and is prone to bright lines and yellowing problems, affecting the stability and service life of photovoltaic modules.
By selecting the appropriate reaction diluent and photoinitiator, adjust the amount of photoinitiator and add gas-phase silica to form a dense crosslinking structure, improve adhesion firmness, reduce oxygen polymerization resistance, improve refractive index matching, and avoid brightening The wires and yellowing are used, and highly reactive resins and monomers are used to speed up the reaction speed.
It realizes rapid photocuring of UV fixing adhesive, improves adhesion and stability, extends service life, enhances the stability of photovoltaic modules, solves the problems of oxygen resistance, bright lines, and yellowing, and improves light utilization Rate.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic cells, and in particular to a UV fixing glue for fixing photovoltaic components, a preparation method and an application thereof. Background Art
[0002] With the continuous development of the photovoltaic industry, new photovoltaic modules are constantly updated. The original PERC process is gradually replaced by HJT and TOPCon processes, and traditional soldering consumes a lot of silver. The stacked grid technology of solar panels prepares a conductive seed layer on the surface of the battery to collect the surface current of the battery cell. An extremely fine triangular conductive wire with ultra-high surface reflectivity is placed above the seed layer, and the conductive seed layer and the conductive wire are connected through conductive connecting materials; this solves the problem of silver consumption to a large extent and reduces costs. The triangular conductive wire is first connected to the battery by welding, and then UV glue is applied to the surface of the battery cell to fix the welding strip to increase the stability of the conduction of the photovoltaic module.
[0003] UV fixing glue is composed of polyurethane acrylic resin, reactive diluent-acrylic monomer, photoinitiator, etc. Polyurethane acrylic resin is one of the important components of UV fixing glue, which determines the mechanical properties and physical properties of UV fixing glue after curing. Polyurethane has high wear resistance, strong adhesion, good flexibility, high peel strength, yellowing resistance and good temperature resistance, and polyacrylate has excellent optical properties and weather resistance, which is suitable for fixing glue for photovoltaic products. The use of suitable polyurethane acrylic resin can solve the problem of aging and yellowing of UV fixing glue to a certain extent, but at 200℃, UV fixing glue will show serious yellowing, affecting the light utilization rate and no longer meeting the use requirements.
[0004] During the curing process of the existing UV adhesive, oxygen in the air will compete with monomers and resins for free radicals to produce oxygen inhibition, which not only affects the efficiency of photocuring, but also leads to poor curing on the surface of the UV adhesive, making it impossible to improve the contact yield between the soldering ribbon and the cell, thus affecting the long-term stability and practicality of the UV adhesive. After lamination, due to the different refractive indices of the UV adhesive, EVA film and glass, defects such as bright lines appear at the fixing points of the UV adhesive with too high a refractive index after lamination, which results in problems such as long curing time, strong oxygen inhibition and short application time during the application of the traditional UV adhesive.
[0005] Therefore, the urgent need to develop a new type of UV fixing glue has become the goal that scientific researchers are working hard for. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a UV fixing glue for fixing photovoltaic modules, a preparation method and an application thereof. By selecting a suitable reaction diluent and a photoinitiator and adjusting the amount of the photoinitiator, the problem of oxygen inhibition during the light curing process of the UV fixing glue and the problem of bright lines and marks appearing at the fixing glue are solved, so as to improve the adhesion firmness of the UV fixing glue and improve the light utilization rate of the photovoltaic module.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: A UV fixing glue for photovoltaic modules, characterized in that it comprises 50-70% by mass of polyurethane acrylic resin, 30-50% by mass of reactive diluent, 1-4% by mass of photoinitiator and 0-2% by mass of fumed silica; The reactive diluent includes an acrylic acid diluent and a mercaptan diluent, and the mass ratio of the acrylic acid diluent to the mercaptan diluent is 0.5:1 to 6:1; The refractive index of the selected polyurethane acrylic resin and acrylic diluent ranges from 1.460 to 1.500; the refractive index of the selected thiol diluent ranges from 1.500 to 1.525.
[0008] Furthermore, the acrylic acid diluent is one or more of dicyclopentallyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, N-acryloylmorpholine, cyclotrimethylolpropane methylal acrylate, tetrahydrofurfuryl acrylate, tetrahydrofurfuryl methacrylate, isobornyl methacrylate, isobornyl acrylate, tricyclodecane dimethanol diacrylate, 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane trimethacrylate, and dipentaerythritol hexaacrylate; the thiol diluent is one or more of trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol tetrakis(3-mercaptopropionate); preferably, in the reactive diluent, the mass proportion of acrylic acid diluent in the UV fixing glue is 15-45%, and the mass proportion of thiol diluent in the UV fixing glue is 5-15%.
[0009] Furthermore, the acrylic acid diluent preferably has the best effect when it is a mixture of 1,6-hexanediol diacrylate and tricyclodecane dimethyl diacrylate, and the mass ratio of the two is 2.5:1-6:1.
[0010] Furthermore, the thiol diluent is pentaerythritol tetrakis (3-mercaptopropionate), and its mass proportion in the UV fixing glue is 6-15%.
[0011] Furthermore, the mass ratio of the acrylic acid diluent to the mercaptan diluent is 0.7:1 to 6:1.
[0012] Furthermore, the photoinitiator is one or more of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 2-hydroxy-2-methyl-1-phenylacetone.
[0013] Furthermore, the photoinitiator is selected from 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the compounding ratio of the two is 1:1~3:1.
[0014] Furthermore, the functionality of the polyurethane acrylic resin is 2 to 3, preferably 2; the viscosity of the UV fixing glue is 8000 to 30000 mPa.s; and the refractive index is between 1.470 and 1.485.
[0015] The method for preparing the UV fixing glue for photovoltaic modules is characterized in that the polyurethane acrylic resin, reactive diluent, photoinitiator and fumed silica weighed according to the raw material ratio are placed in a vacuum mixer and stirred; the mixed glue is then irradiated under a light source of 250-420 nm for not less than 5 seconds, and the cross-linking polymerization of the polyurethane acrylate and the reactive diluent is initiated under the action of the photoinitiator to form a dense cross-linked structure.
[0016] The application of the UV fixing glue is characterized in that it is used for bonding the soldering strip and the battery cell. The UV fixing glue is applied to the surface of the battery cell and the soldering strip by dispensing, printing or coating, and the UV fixing glue is cured by light curing.
[0017] The UV fixing adhesive of the present invention uses polyurethane acrylate as a light-curing resin prepolymer. Since polyurethane acrylate contains acrylic functional groups and urethane bonds, polyacrylate has excellent optical properties and weather resistance; polyacrylate has high wear resistance, strong adhesion, good flexibility, high peel strength, and excellent yellowing resistance and temperature resistance. Acrylic acid in the reactive diluent participates in the reaction to form a dense cross-linked network structure. The cured adhesive also has the excellent properties of acrylic acid and polyurethane.
[0018] The present invention improves the oxygen inhibition problem in the curing process of UV fixing glue by increasing the amount of photoinitiator, adding thiol, and using highly active resins or monomers. Excessive photoinitiators can generate more free radicals, prevent the consumption of oxygen and prevent the diffusion of oxygen to the coating, thereby overcoming oxygen inhibition; during the curing process of UV glue, thiol reacts with oxygen to consume oxygen and reduce the inhibition of oxygen on UV glue; highly active resins or monomers will accelerate the reaction speed, thereby improving oxygen inhibition. It can be cured by ultraviolet irradiation with a wavelength of 356nm for 5s, which improves production efficiency, and there is no oxygen inhibition and no shrinkage. The energy value of irradiation under a 365nm ultraviolet lamp for 5s is 1400~7000mJ / cm 2 , reducing the energy required for light curing and saving energy consumption.
[0019] At the same time, the present invention also reduces the use of resins or monomers with high refractive indices. The refractive indices of the resins or monomers used are in the range of 1.460 to 1.500, and the range of the thiol diluent is 1.500 to 1.525, so that the refractive index of the prepared glue is between 1.470 and 1.485, thereby solving the problem of bright lines and marks on the edges of UV fixing glue.
[0020] Use colorless, transparent, yellowing-resistant, high temperature-resistant, water-resistant, and tough resins and monomers to extend the light resistance of UV glue, avoid yellowing, and solve the problem of UV fixing glue marks. The UV fixing glue provided by the present invention is baked in an oven at 150°C for 0.5h, 1h, 2h, and 3h without yellowing, and the light transmittance can reach more than 90%.
[0021] The UV fixing glue of the present invention has no yellowing phenomenon during the long-term high-temperature aging process, and the visible light transmittance remains above 90%. It is extremely suitable for the application of photovoltaic modules. At the same time, it can be quickly cured under UV light irradiation, has high adhesion, enhances the stability of photovoltaic modules, and makes an important contribution to the development of "grid stacking" technology. The use of this UV fixing glue will not change the conductivity and appearance of the photovoltaic module. On the original basis, it can enhance the stability of the photovoltaic module and extend its service life. It can enhance the stability of the photovoltaic module.
[0022] Compared with traditional UV adhesive, the UV fixing adhesive of the present invention has excellent characteristics such as high reactivity, strong bonding force, good toughness, yellowing resistance, high temperature resistance, high light transmittance, etc. It is applied to the bonding field of welding strips and solar cells, plays the role of fixing welding strips, enhancing the stability of photovoltaic modules and extending service life. At the same time, it also broadens the application field of UV fixing adhesive. DETAILED DESCRIPTION
[0023] Embodiment 1
[0024] Weigh 7.5g polyurethane acrylic resin (refractive index: 1.475), 0.8g trimethylolpropane tris (3-mercaptopropionate) (refractive index: 1.512), 3g cyclotrimethylolpropane methyl acrylate, 0.2g 1-hydroxycyclohexyl phenyl ketone, 0.2g 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 0.5g isobornyl methacrylate, 1g tricyclodecane dimethanol diacrylate. After rotating in a vacuum stirrer for 10 min, irradiate under 365 nm ultraviolet light for 5s. Glue refractive index: 1.477; glue viscosity 8750 mPa.s; component test results: slight oxygen inhibition, no bright line after lamination, no color difference problem. Embodiment 2
[0025] Weigh 8g polyurethane acrylic resin (refractive index: 1.475-1.489), 1.4g pentaerythritol tetrakis (3-mercaptopropionate) (refractive index: 1.525), 1g cyclotrihydroxymethylpropane methyl acrylate, 0.3g 1-hydroxycyclohexyl phenyl ketone, 0.1g 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 0.5g isobornyl methacrylate, 1.5g tricyclodecane dimethanol diacrylate, 2.2g dipropylene glycol diacrylate. After rotating in a vacuum stirrer for 10 min, irradiate under 365 nm ultraviolet light for 6s. Glue refractive index: 1.475; glue viscosity 8150 mPa.s; component test results: slight oxygen inhibition, no bright line after lamination, no color difference problem. Embodiment 3
[0026] Weigh 12g polyurethane acrylic resin (refractive index: 1.475-1.485), 2g pentaerythritol tetra(3-mercaptopropionate), 3.9g 1,6-hexanediol diacrylate, 1.5g tricyclodecane dimethanol diacrylate, 0.5g 1-hydroxycyclohexyl phenyl ketone, 0.1g fumed silica. After rotating in a vacuum stirrer for 10 min, irradiate under 365 nm UV for 5s. Glue refractive index: 1.474; glue viscosity 8950 mPa.s; component test results: no oxygen inhibition, no bright line after lamination, no color difference problem, no PCT aging problem. Embodiment 4
[0027] Weigh 12g polyurethane acrylic resin (refractive index: 1.475-1.485), 1.3g pentaerythritol tetra(3-mercaptopropionate), 4.5g 1,6-hexanediol diacrylate, 1.5g tricyclodecane dimethanol diacrylate, 0.5g 1-hydroxycyclohexyl phenyl ketone, 0.2g fumed silica. After rotating in a vacuum agitator for 10 min, irradiate under 250 nm UV for 10s. Glue refractive index: 1.478; glue viscosity 8500 mPa.s; component test results: no oxygen inhibition, no bright line after lamination, no color difference problem, no PCT aging problem. Embodiment 5
[0028] Weigh 14g polyurethane acrylic resin (refractive index: 1.475-1.485), 3g pentaerythritol tetra(3-mercaptopropionate), 1.5g 1,6-hexanediol diacrylate, 0.6g tricyclodecane dimethanol diacrylate, 0.8g 1-hydroxycyclohexyl phenyl ketone, 0.1g fumed silica. After rotating in a vacuum stirrer for 10 min, irradiate under 420 nm UV for 5s. Glue refractive index: 1.484; glue viscosity 20350 mPa.s; component test results: no oxygen inhibition, no bright line after lamination, no color difference problem, no PCT aging problem. Embodiment 6
[0029] Weigh 13g polyurethane acrylic resin (refractive index: 1.475-1.485), 2.5g pentaerythritol tetra(3-mercaptopropionate), 3g 1,6-hexanediol diacrylate, 0.5g tricyclodecane dimethanol diacrylate, 0.5g 1-hydroxycyclohexyl phenyl ketone, 0.5g fumed silica. After rotating in a vacuum stirrer for 10 min, irradiate under 365 nm UV for 6s. Glue refractive index: 1.481; glue viscosity 27400 mPa.s; component test results: no oxygen inhibition, no bright line after lamination, no color difference problem, no PCT aging problem. Comparative Example 1
[0030] Weigh 8.5g polyurethane acrylic resin (refractive index: 1.475-1.489), 1.4g pentaerythritol tetrakis (3-mercaptopropionate) (refractive index: 1.525), 1g cyclotrimethylolpropane methyl acrylate, 0.3g 1-hydroxycyclohexyl phenyl ketone, 0.1g 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 0.5g isobornyl methacrylate, 1.2g tricyclodecane dimethanol diacrylate, 2g dipropylene glycol diacrylate, 0.025g triethanolamine. After rotating in a vacuum stirrer for 10 min, irradiate under 365 nm ultraviolet light for 5s. No oxygen inhibition, but the colloid is very yellow. Comparative Example 2
[0031] Weigh 10g polyurethane acrylic resin (refractive index: 1.480-1.486), 5g cyclotridecane dimethanol diacrylate (refractive index: 1.501), 3.5g pentaerythritol tetra(3-mercaptopropionate), 0.4g hydroxycyclohexane phenone, 0.5g isobornyl methacrylate, 8g cyclotrihydroxymethylpropane methyl acrylate. After rotating in a vacuum stirrer for 10 min, irradiate under 365 nm ultraviolet for 6s. Glue refractive index: 1.484; glue viscosity 4950 mPa.s; component test results: no oxygen inhibition, obvious colloid bright line after lamination, and color difference problem.
[0032] Finally, it should be pointed out that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents, and these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A UV fixing glue for photovoltaic modules, characterized in that: It includes 50-70% by mass of polyurethane acrylic resin, 30-50% by mass of reactive diluent, 1-4% by mass of photoinitiator and 0-2% by mass of fumed silica; The reactive diluent includes an acrylic acid diluent and a mercaptan diluent, and the mass ratio of the acrylic acid diluent to the mercaptan diluent is 0.5:1 to 6:1; The refractive index of the selected polyurethane acrylic resin and acrylic diluent ranges from 1.460 to 1.500; the refractive index of the selected thiol diluent ranges from 1.500 to 1.
525.
2. The UV fixing adhesive for photovoltaic modules according to claim 1, characterized in that: The acrylic acid diluent is one or more of dicyclopentallyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, N-acryloyl morpholine, cyclotrimethylolpropane methylal acrylate, tetrahydrofurfuryl acrylate, tetrahydrofurfuryl methacrylate, isobornyl methacrylate, isobornyl acrylate, tricyclodecane dimethanol diacrylate, 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane trimethacrylate, and dipentaerythritol hexaacrylate; the thiol diluent is one or more of trimethylolpropane tris (3-mercaptopropionate) and pentaerythritol tetrakis (3-mercaptopropionate); preferably, in the reactive diluent, the mass fraction of the acrylic acid diluent in the UV fixing glue is 15-45%, and the mass fraction of the thiol diluent in the UV fixing glue is 5-15%.
3. The UV fixing adhesive for photovoltaic modules according to claim 2, characterized in that: The acrylic acid diluent is preferably a compound of 1,6-hexanediol diacrylate and tricyclodecane dimethyl diacrylate, and the mass ratio of the two is 2.5:1-6:
1.
4. The UV fixing adhesive for photovoltaic modules according to claim 2, characterized in that: The thiol diluent is pentaerythritol tetrakis (3-mercaptopropionate), and its mass proportion in the UV fixing glue is 6-15%.
5. The UV fixing adhesive for photovoltaic modules according to claim 1, characterized in that: The mass ratio of acrylic acid diluent to mercaptan diluent is 0.7:1~6:
1.
6. The UV fixing adhesive for photovoltaic modules according to claim 1, characterized in that: The photoinitiator is one or more of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 2-hydroxy-2-methyl-1-phenylacetone.
7. The UV fixing adhesive for photovoltaic modules according to claim 1, characterized in that: The photoinitiator is selected from 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the compounding ratio of the two is 1:1-3:
1.
8. The UV fixing adhesive for photovoltaic modules according to claim 1, characterized in that: The functionality of the polyurethane acrylic resin is 2-3, preferably 2; the viscosity of the UV fixing glue is 8000-30000 mPa.s; and the refractive index is between 1.470 and 1.
485.
9. The method for preparing a UV fixing adhesive for photovoltaic modules according to any one of claims 1 to 9, characterized in that: The polyurethane acrylate resin, reactive diluent, photoinitiator and fumed silica weighed according to the raw material ratio are placed in a vacuum mixer and stirred; the mixed glue is then irradiated under a light source of 250~420nm for not less than 5s, and the cross-linking polymerization of the polyurethane acrylate resin and the reactive diluent is initiated under the action of the photoinitiator to form a dense cross-linking structure.
10. The use of the UV fixing glue according to any one of claims 1 to 9, characterized in that: Used for bonding the soldering tape and the battery cell, the UV fixing glue is applied to the surface of the battery cell and the soldering tape by dispensing, printing or coating, and the UV fixing glue is cured by light curing.
Citation Information
Cited By
Photovoltaic UV adhesive and preparation method thereof
CN120118654A